Implementation of Principal Academic Supervision to Improve the Quality of Learning in Elementary Schools - Ilmiadin; Niswanto; Suparta Rasyid; Emamalini (LPPM Undiksha, 2025)
Many elementary schools face challenges with the effectiveness of the learning process, leading to low student motivation and learning outcomes. This study aims to analyze the implementation of academic supervision to improve learning quality in an effective and efficient manner. This study employed a qualitative research design, using a descriptive qualitative approach. The subjects of this study were principals, teachers, and staff involved in the management and implementation of academic supervision in elementary schools. Participants were selected purposively, resulting in a total of 20 subjects. Data collection methods used observation, interviews, and documentation. The research instruments consisted of interview and observation guidelines. Data analysis techniques in this study included transcription, coding, theme identification, data interpretation, result presentation, and the establishment of analytical validity and reliability. Data analysis was conducted using the Miles and Huberman qualitative analysis model. The results of the study indicate that academic supervision is implemented through planning with teachers, classroom observations, and the examination of learning materials, and is evaluated through the provision of individual and group feedback. The implementation of routine, constructive supervision has been proven to help teachers improve their learning materials, apply a wider range of teaching methods, and increase student engagement in the learning process. The implications of these findings confirm that structured, collaborative, and ongoing academic supervision plays an important role as a principal's strategy in improving teacher professionalism and the quality of learning in elementary schools.